2018
DOI: 10.1111/cas.13778
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long noncoding RNA associated‐competing endogenous RNA as prognostic biomarkers in clear cell renal carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most common malignant carcinomas and its molecular mechanisms remain unclear. Long noncoding RNA (lncRNA) could bind sites of miRNA which affect the expression of mRNA according to the competing endogenous (ceRNA) theory. The aim of the present study was to construct a ceRNA network and to identify key lncRNA to predict survival prognosis. We identified differentially expressed mRNA, lncRNA and miRNA between tumor tissues and normal tissues from The Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
(72 reference statements)
2
28
1
Order By: Relevance
“…The SCCT cases data of clinical and RNA expression were collected from TCGA database. The exclusion criteria were including: (i) histological diagnosis was not SCCT; (ii) no complete data (including gender, age, survival status, stage, and survival time) for analysis [28]. 118 SCCT patients were enrolled in the study.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…The SCCT cases data of clinical and RNA expression were collected from TCGA database. The exclusion criteria were including: (i) histological diagnosis was not SCCT; (ii) no complete data (including gender, age, survival status, stage, and survival time) for analysis [28]. 118 SCCT patients were enrolled in the study.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…It has been known that lncRNAs can act as ceRNAs to bind with target miRNAs. 7,8 Therefore, we speculated that LINC00473 might regulate radiosensitivity of ESCC cells via this mechanism. By searching LncBase (http://carolina.imis.athena-innovation.…”
Section: Mir-374a-5p Was Targeted By Linc00473 and Downregulated Inmentioning
confidence: 99%
“…Numerical evidence pronounce that lncRNAs can associate with miRNA to weaken the effects of miRNA on in mediating mRNA expression 20 . Some recent studies have suggested that aberrant lncRNA expression is associated with ccRCC, and many potential biomarkers have been uncovered in ccRCC [21][22][23] . However, these results rely on a temporary TCGA database that lacks external www.nature.com/scientificreports/ validation sets, hence, it poses difficulty in assessing the accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%